Improving Social Skills of Elementary Students Through Interactive Learning Methods at SD Negeri 1 Lawawoi - Burhan, Imron; Musfirah, Musfirah; Iyan, Iyan; Usman, Usman; Sultan, Muhammad Asrul (Help: Journal of Community Service, 2025)
This community service program aimed to enhance the social skills of students at SD Negeri 1 Lawawoi, Sidenreng Rappang Regency, focusing on expressing gratitude, asking for help, apologizing, and forgiving. The activity was conducted on November 21, 2024, involving 25 students, the Principal, and teachers. A combination of lecture and role-playing methods was used to deliver the material interactively. The program was implemented in three main stages: preparation, implementation, and reflection. During the preparation stage, the team coordinated with school authorities and developed appropriate learning materials. In the implementation stage, students engaged in interactive lectures and role-playing scenarios that simulated real-life social situations, allowing them to practice and internalize the skills effectively. The reflection stage encouraged students to share their experiences and discuss the benefits of maintaining positive social relationships. Feedback from students and teachers indicated significant improvements in students' confidence and ability to manage social interactions. However, the limited duration and number of participants were recognized as potential limitations of the program. Future recommendations include extending the program duration, involving more participants, and conducting follow-up studies to assess the long-term impact of the training. The overall results suggest that integrating interactive learning methods with reflective practices can significantly enhance students' social skills.